Two Phosphodiesterases from Ustilago Maydis Share Structural and Biochemical Properties with Non-Fungal Phosphodiesterases - Agarwal, Charu; Schultz, David J.; Perlin, Michael H. (Frontiers in Microbiology, 2010)
The dependence of Protein Kinase A (PKA) activity on cAMP levels is an important facet of the dimorphic switch between budding and filamentous growth as well as for pathogenicity in some fungi. To better understand these processes in the pathogenic fungus Ustilago maydis, we characterized the structure and biochemical functions of two phosphodiesterase (PDE) genes. Phosphodiesterases are enzymes involved in cAMP turnover and thus, contribute to the regulation of the cAMP-PKA signaling pathway. Two predicted homologues of PDEs were identified in the genome of U. maydis and hypothesized to be involved in cAMP turnover, thus regulating activity of the PKA catalytic subunit. Both umpde1 and umpde2 genes contain domains associated with phosphodiesterase activity predicted by InterPro analysis. Biochemical characterization of recombinantly produced UmPde1 (U. maydis Phosphodiesterase I) and UmPde2 demonstrated that both enzymes have phosphodiesterase activity in vitro, yet neither was inhibited by the phosphodiesterase inhibitor IBMX. Moreover, UmPde1 is specific for cAMP, while UmPde2 has broader substrate specificity, utilizing cAMP and cGMP as substrates. In addition, UmPde2 was also found to have nucleotide phosphatase activity that was higher with GMP compared to AMP. These results demonstrate that UmPde1 is a bona fide phosphodiesterase, while UmPde2 has more general activity as a cyclic nucleotide phosphodiesterase and/or GMP/AMP phosphatase. Thus, UmPde1 and UmPde2 likely have important roles in cell morphology and development and share some characteristics with a variety of non-fungal phosphodiesterases.